READING AS AN ART OF THINKING IMPLEMENTING THE CONCEPT OF HOW TO READ A BOOK IN SOCIAL STUDIES LEARNING IN ELEMENTARY SCHOOLS - Tiara Trirahmayati; Aramudin (El Midad, 2025)
Reading literacy is a fundamental competence in elementary education, particularly in Integrated Social Studies learning, which requires students to understand not only textual information but also the social meanings embedded in texts. Reading should therefore be positioned as an art of thinking that involves comprehension, analysis, and reflection. This study aims to describe the implementation of the “How to Read a Book” concept as an art of thinking in Integrated Social Studies instruction for fifth-grade elementary students. The background of this study is the tendency in Social Studies learning to emphasize memorization, leading to Reading activities that do not optimally develop students’ analytical and reflective abilities. This research employed a descriptive, qualitative method with a field study approach, using classroom observation, semi-structured interviews, and documentation. The results indicate that Reading activities in Integrated Social Studies learning have been systematically integrated through guided Reading practices, including initial Reading, analytical Reading, and reflective discussion. Teachers guided students in identifying key ideas, interpreting social concepts, and relating Reading content to real-life contexts. Reading activities were not limited to understanding factual information; they also aimed to develop reasoning, critical thinking, and social awareness. The study concludes that the implementation of Reading as an art of thinking through the How to Read a Book concept contributes to meaningful literacy practices and supports the development of critical and reflective thinking skills in elementary school students.